2022
DOI: 10.3389/fimmu.2022.779888
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Activation Signals Modulate Cytoskeletal Dynamics and Mechanical Force Generation

Abstract: Cytotoxic T lymphocytes (CTLs) play an integral role in the adaptive immune response by killing infected cells. Antigen presenting cells (APCs), such as dendritic cells, present pathogenic peptides to the T cell receptor on the CTL surface and co-stimulatory signals required for complete activation. Activated CTLs secrete lytic granules containing enzymes that trigger target cell death at the CTL-target contact, also known as the immune synapse (IS). The actin and microtubule cytoskeletons are instrumental in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 113 publications
0
12
0
Order By: Relevance
“… 28 , 29 Previous studies have shown that microtubules influence many cellular functions, including cytokine secretion and vesicular and organelle transport. 30 , 31 Cooley et al reported that reduced INF‐γ release from activated global SPAG6‐deficient mice CD8 + T cells was due to defective secretion. 32 Interestingly, in the present study, downregulation or forced expression of SPAG6 affected the concentrations of cytokines in the supernatant of the cell culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 Previous studies have shown that microtubules influence many cellular functions, including cytokine secretion and vesicular and organelle transport. 30 , 31 Cooley et al reported that reduced INF‐γ release from activated global SPAG6‐deficient mice CD8 + T cells was due to defective secretion. 32 Interestingly, in the present study, downregulation or forced expression of SPAG6 affected the concentrations of cytokines in the supernatant of the cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines contribute to the development of debilitating symptoms associated with the disease and fuel the selective expansion of the neoplastic clone 28,29. Previous studies have shown that microtubules influence many cellular functions, including cytokine secretion and vesicular and organelle transport 30,31. Cooley et al reported that reduced INFγ release from activated global SPAG6-deficient mice CD8 + T cells was due to defective secretion 32.…”
mentioning
confidence: 99%
“…As MHC-I molecules feature on every nucleated cell of the organism, they visualize pathological processes that occur in the organism at an early stage. Peptide presentation on MHC-I molecules, recognition by T-cell receptors (TCR), and immune cell activation are three stages in which cell interactions are inspected for affinity binding and initial signal strength, duration of stimulation, and decay ( Segura et al., 2008 ; Pathni et al., 2022 ). Historically, the MHC-I system has been linked to transplant immunology and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments using pharmacological perturbation of actin nucleation factors suggest that the mechanosensing activity of the antigen receptor is supported by the cortical actin cytoskeleton within the lymphocytes 5,9,11 , [21][22][23][24][25][26][27][28] . However, molecular mechanisms within the lymphocytes that connect antigenpresenting surface mechanics to the underlying cytoskeleton remain unknown.…”
Section: Introductionmentioning
confidence: 99%